The effect of non-specific tight junction modulators on the transepithelial transport of poorly permeable drugs across airway epithelial cells. (21st April 2017) - Ghadiri, Maliheh; Young, Paul M.; Jarolimek, Wolfgang; Grau, Georges E. R.; Oliver, Brian G. G.; Traini, Daniela
Abstract: The epithelial barrier in the respiratory system is a major obstacle for drug delivery to the systemic circulation in the lung. Epithelial barrier hinders the transport of large macromolecules or polar drugs. Essential components of this epithelial fence are physical intercellular structures termed tight junctions. Therefore, modulating tight junctions can enhance paracellular transport across epithelial barrier. In this study, the effect of some of non-specific tight junction modulators (TJMs); (Sodium (Na) decanoate, oleic acid and ethyleneglycol-bis-(β-aminoethyl ether)-N, N′-tetraacetic acid (EGTA)) with established effect on intestinal tight junctions was evaluated for its effects on bronchial epithelial cells (Calu-3 cells). It was demonstrated that the effect of TJMs especially Na decanoate resulted in a reversible opening of tight junctions evidenced by the decrease in the transepithelial resistance. It was also demonstrated that this reduction of TEER upon exposing the epithelial cells to the TJMs resulted in a significant increase in Flu-Na (paracellular marker) and PXS25 (anti-fibrotic compound) transepithelial transport through this barrier. In conclusion, among the investigated non-specific TJMs, Na decanoate fulfilled the requirements of an effective, non-toxic and reversible tight junction modulator for Calu-3 lung epithelial cells.